2021
DOI: 10.1371/journal.pone.0261593
|View full text |Cite
|
Sign up to set email alerts
|

Design and analysis of a performance monitoring system for a seed metering device based on pulse width recognition

Abstract: To realize real-time and accurate performance monitoring of large- and medium-sized seed metering devices, a performance monitoring system was designed for seed metering devices based on LED visible photoelectric sensing technology and a pulse width recognition algorithm. Through an analysis of the of sensing component pointing characteristics and seed motion characteristics, the layout of the sensing components and critical photoelectric sensing system components was optimized. Single-grain seed metering devi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…The model was constructed with 10 filled spheres. The filling diagram is shown in Figure 9, and the Poisson's ratio of the seeds was set to 0.4, the shear modulus was 1.37×10 8 Pa, and the density was 197 kg/m 3 [28][29][30] .…”
Section: Simulation Analysis Of Seed Guiding Process Based On Edem 24...mentioning
confidence: 99%
“…The model was constructed with 10 filled spheres. The filling diagram is shown in Figure 9, and the Poisson's ratio of the seeds was set to 0.4, the shear modulus was 1.37×10 8 Pa, and the density was 197 kg/m 3 [28][29][30] .…”
Section: Simulation Analysis Of Seed Guiding Process Based On Edem 24...mentioning
confidence: 99%
“…In 2021, our group developed a performance monitoring system for a seed metering device for large-and medium-sized grain crops. The test results showed that the system had an accuracy of 98.92% for missed seeding quantity monitoring at a seeding speed of 10 km/h [28]. The missed seeding detection system is not the main focus of this study as the system primarily serves to support the compensation system in generating the compensation decision.…”
Section: Introductionmentioning
confidence: 99%
“…The stability of the operation of the electric energy metering device is also closely related to the working efficiency of both parties. It can be seen that in order to realize the smooth operation of power supply enterprises [2], the electric energy metering device is one of the most necessary basic conditions [3]. With the characteristics of patrol inspection data, the diagnosis of the state of electric energy metering devices is realized, and the corresponding identification results are highly reliable.…”
Section: Introductionmentioning
confidence: 99%